An Empirical Assessment of Technology Adoption Model in E-Commerce - Nanda Pretty Amalia Zakiah; Evanitha Kurrata Aini; Ferdy Ferdy; Muhammad Ali Fikri; Gan Xinxin (Proceedings Series on Social Sciences & Humanities, 2024)
Background: Over the past few decades, e-commerce has become one part of the development of electronic commerce technology. The development has caused customers' online purchasing habits to change. This research analyzes how e-commerce can be made more efficient and profitable and achieve business goals by using the Technology Acceptance Model (TAM) as a theoretical framework. Method: Data were examined using Smart's Partial Least Square (PLS) method. The widely used TAM is preferred as a suitable hypothetical model to examine how well the development of electronic commerce technology to support e-commerce. Results: The findings demonstrated that attitudes about and behavioral intentions to use were positively impacted by perceived usefulness. Research indicates that attitudes about utilizing are positively impacted by perceived ease of use, while behavioral intention to use is negatively impacted. It has also been demonstrated that behavioral intention to use is positively impacted by attitude toward usage. It has also been demonstrated that attitudes toward usage modulate the effects of perceived utility and perceived ease of use on behavioral intention to use. Conclusion: This research extends the theoretical and applied understanding needed to apply the TAM model in the e-commerce industry. This research enables business owners to better and more effectively utilize electronic commerce technology.